Inisiasi Pengembangan Induk Bank Sampah Cawas - Gatot Supangkat Samidjo; Bambang Heri Isnawan; Triyono Triyono (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Cawas Village has launched a Garbage Bank in every RW in its area, one of which is RW 09 Kuncen, which has succeeded in establishing the Manunggal Sejahtera Waste Bank. The focus of this program is the development of a waste bank to become the Parent Garbage Bank, both in management and in technical implementation. The objective of this activity is the compilation of the Cawas Village Kuncen Waste Bank Master Development Plan which is in line with the Cawas Village RPJMDes regarding waste management, both inorganic and organic. The Direct Action method is applied in community service programs by increasing management capabilities through socialization activities, training, practice, study visits, and Waste Bank Master planning documents preparation. The presence of the Covid-19 pandemic diverted some community empowerment activities to community efforts in overcoming Covid-19. Community empowerment is done online. The results achieved have not been optimal due to the Covid-19 pandemic, so that several strategic activities related to the initiation of the main waste bank development have been hampered. Some of the results were achieved, the agreement to build a waste bank was continued after the pandemic, a demonstration area for the reuse of waste as a planting place, preparation and implementation of an environmental competition for waste management, and activities to prevent the spread of Covid-19 (environmental sanitation and checking body temperature at the entrance to villages and mosques). The response of partner satisfaction to program implementation is above 80%, and 100% hope that it will continue